The Hadith of Rukyatu al-Hilāl and Its Contextualization According to the Maqāşid As-Syarī’ah Perspective - Fajar Rachmadhani (IJISH (International Journal of Islamic Studies and Humanities), 2020)
The purpose of this research is to discuss the urgency of the understanding of hadith rukyatu al-hilāl in a more comprehensive and contextual manner within the framework of Maqāshid Syarīah. This is because the understanding of the hadith rukyatu al-hilāl has an impact on the method of determining the entry of the early qamariyah months, especially those related to worship such as the fasting of Ramadhan, Eid al-Fitr and Eid al-Adha. There are many hadith about the Prophet's order to see the new moon in order to find out the entry of the fasting month of Ramadan as well as the Eid-ul-Fitr festivities, because rukyat at that time was the only method for determining the entry earlier that month.  There is no doubt that the aim of Islamic law is to realize the benefit of mankind in the world and the hereafter and keep away all forms of difficulties. While, understanding the hadith of the rukyatu al-hilāl and its implementation textually sometimes cause confusion and difficulties as well as differences that often occur in the determination of the beginning of the month of qamariayah, especially those related to fasting, Eid al-Fitr and Eid al-Adha.